Development of entrepreneurship in Ayesha Abed Foundation, Manikganj - Ayesha Abed Foundation, BRAC (© BRAC, 2016)
1. Entrepreneurship in economic enterprises 2. AAF as enterprise 3. Conflict in goals 4. AAF's working definition of Entrepreneurship 5. Discussion 6. Challenges for management